Resistance and heteroresistance to colistin among multidrug-resistant and extensively drug-resistant Gram-negative organisms isolated from patients admitted to Zagazig University Hospitals - Salah Al-Sayed Ibrahim Ali; Aya Ahmed Ghamry; Seham K Khirala; Asmaa M El-Nasser; Fatma M Attia Al-Sayed; Fatma Atef Ibrahim (Journal of Infection in Developing Countries)
Introduction: Nowadays, treating serious infections caused by multi-drug resistant Gram-negative bacteria is best left to the antiquated medication "colistin.". There have been reports of colistin-resistant (Col-R) and heteroresistant (hR) MDR and XDR-GNB strains worldwide. Therefore, we aimed to ascertain the rate of colistin resistance, certain potential resistance mechanisms, and heteroresistance in colistin-susceptible (Col-S) clinical isolates.